Abnormalities in the white matter tracts in patients with Parkinson disease and psychosis. (5th May 2020) - Lenka, Abhishek; Ingalhalikar, Madhura; Shah, Apurva; Saini, Jitender; Arumugham, Shyam Sundar; Hegde, Shantala; George, Lija; Yadav, Ravi; Pal, Pramod Kumar
Abstract : Objective: The objective of the current study was to compare the microstructural integrity of the white matter (WM) tracts in patients having Parkinson disease (PD) with and without psychosis (PD-P and PD-NP) through diffusion tensor imaging (DTI). Methods: This cross-sectional study involved 48 PD-NP and 42 PD-P who were matched for age, sex, and education. Tract-based spatial statistics (TBSS) was used to compare several DTI metrics from the diffusion-weighted MRIs obtained through a 3-Tesla scanner. A set of neuropsychological tests was used for the cognitive evaluation of all patients. Results: The severity and stage of PD were not statistically different between the groups. The PD-P group performed poorly in all the neuropsychological domains compared with the PD-NP group. TBSS analysis revealed widespread patterns of abnormality in the fractional anisotropy (FA) in the PD-P group, which also correlated with some of the cognitive scores. These tracts include inferior longitudinal fasciculus, inferior fronto-occipital fasciculus, right parieto-occipital WM, body of the corpus callosum, and corticospinal tract. Conclusion: This study provides novel insights into the putative role of WM tract abnormalities in the pathogenesis of PD-P by demonstrating significant alterations in several WM tracts. Additional longitudinal studies are warranted to confirm the findings of our research.